THE EFFECT OF PALM OIL ASH AND CHICKEN MANURE ON GROWTH AND YIELD ON DAYAK ONION IN PEAT SOIL - particia jasmin; siti hadijah; tatang abdurrahman (Fakultas Pertanian Universitas Tanjungpura, 2019)
The aim of this study was to obtain the best dose of the effect of palm oil ash and chicken manure interaction as well as the best dosage of single factor palm oil ash and chicken manure on growth and yield of dayak onion in peat soil. This research was conducted from October 21, 2018 to January 21, 2019 in the experimental garden of the Faculty of Agriculture, Tanjungpura University, Pontianak. This study used the Factorial method with a completely randomized design (CRD) pattern with 2 treatment factors. The first factor was the provision of palm oil ash consisting of two levels, namely 109.50 g and 138.85 g. The second factor was the provision of chicken manure consisting of 3 levels, namely 40 g, 60 g, and 80 g. The variables observed in this study were plant height, number of leaves, number of tillers, number of tubers, fresh weight of tubers and weight of dry tubers.The results showed that there was no interaction between the administration of palm oil ash and chicken manure to all the observed variables of dayak onion plants. The administration of palm oil ash gives the same results on all observation variables of onion dayak plants. Providing chicken manure can affect the number of tillers. The best dose of chicken manure is 60 g / polybag, equivalent to 15 tons / ha. The effect of effective combination occurs on the administration of palm oil ash doses of 109,50 g / polybag and chicken manure dose of 60 g / polybag.Keywords : chicken manure, dayak onion, palm oil ash, peat soil